Penerapan Metode Diskusi Untuk Meningkatkan Hasil Belajar di SD Muhammadiyah 01 Babat - Sarah Almaida Almaida; Septya Khusnia Putri; Andy Rahmat Prayogo; Apmad Apmad Ipvmawan Kharisma (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The research carried out was Classroom Action Research. The purpose of conducting this classroom action research is to improve and improve the practice that should be done by the teacher. The average score of learning outcomes in the initial reflection I reached 68.39 Of the 31 students in the high school class of SDM 01 Babat students were able to achieve scores in accordance with the KKM. Thus classical completeness was only achieved as much as 54.84%. Referring to these results, the average learning outcomes, absorption and classical learning completeness have not met the predetermined targets. Therefore, learning outcomes can be improved through the application of the discussion method in the learning process. Because the observation results of cycle 1 and cycle 2 can state that the discussion method can improve learning outcomes in students of SDM 01 Babat. Because of the increase in reflection in cycle II by 70% with an average student learning outcome of 81.29 so that it can be said to be successful.